Competitive adsorption of pollutants from anodizing wastewaters to promote water reuse. (1st September 2021) - Acosta-Herrera, Andrea Alejandra; Hernández-Montoya, Virginia; Castillo-Borja, Florianne; Pérez-Cruz, María A.; Montes-Morán, Miguel A.; Cervantes, Francisco J.
Abstract: Anodizing wastewater contains principally phosphate (PO4 3− ) anions according to previous studies, but with the purpose to promote water reuse in this type of industry, a complete characterization of wastewater was made to remove other anions and cations also present in significant concentration. Particularly, the adsorption of sodium (Na + ), potassium (K + ), fluoride (F − ), sulfate (SO4 2− ) and phosphate (PO4 3− ) was studied using different sorbents such as: coconut shell activated carbon, bone char, bituminous coal activated carbon, natural zeolite, silica, anionic and cationic exchange resins, a coated manganese-calcium zeolite, coconut shell activated carbon containing iron and iron hydroxide. All sorbents were characterized using FT-IR spectroscopy, potentiometric titration, nitrogen adsorption isotherms at 77 K, X-ray diffraction and SEM/EDX analysis to study the adsorption mechanism. The adsorption studies were performed in batch systems under constant agitation using both standard solutions of each ion and real anodizing wastewater. Results showed that, in general, the adsorption of all anions and cations is higher when mono-component standard solutions were used, since in the anodizing wastewater all species are competing for the active sites of the adsorbent. Na + present in anodizing wastewater was efficiently adsorbed on coated manganese-calcium zeolite (20.55 mg/g) and natural zeolite (18.55 mg/g); while K + was poorly adsorbed on all sorbents (less than 0.20 mg/g). Anions such as F −, SO4 2− and PO4 3−, were better adsorbed on the anionic resin (0.17, 45.38 and 2.92 mg/g, respectively), the iron hydroxide (0.14, 7.96 and 2.87 mg/g, respectively) and the bone char (0.34, 8.71 and 0.27 mg/g, respectively). All these results suggest that adsorption is a promising tertiary treatment method to achieve water reuse in the anodizing industry. Graphical abstract: Image 1 Highlights: Anodizing wastewater contains principally phosphates, sulphates, and sodium ions. Natural and modified zeolites efficiently remove sodium from anodizing wastewater. The best anions adsorbents are iron hydroxide and materials with hydroxyapatite. Adsorption mechanisms of anions are ion exchange and electrostatic interaction.